2014
DOI: 10.1016/j.jalz.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular network alterations in the retina of patients with Alzheimer's disease

Abstract: Patients with AD have altered microvascular network in the retina (narrower retinal venules and a sparser and more tortuous retinal vessels) compared with matched nondemented controls. These changes in retinal microvasculature may reflect similar pathophysiological processes in cerebral microvasculature in the brains of patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
254
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(274 citation statements)
references
References 48 publications
13
254
4
3
Order By: Relevance
“…In addition, one study using SD-OCT showed a diffuse reduction of the RNFL and GCL combined in AD [49], although the authors were not able to determinate which layer was most affected by AD. Later studies have demonstrated IPL thinning in AD patients [41,50,52,56,57]. This reduction of ganglion cell complex thickness (GC-IPL and RNFL layers) in AD occurs to a larger extent than that accounted for age-related GC-IPL loss alone (about 0.3 μm/ year) [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one study using SD-OCT showed a diffuse reduction of the RNFL and GCL combined in AD [49], although the authors were not able to determinate which layer was most affected by AD. Later studies have demonstrated IPL thinning in AD patients [41,50,52,56,57]. This reduction of ganglion cell complex thickness (GC-IPL and RNFL layers) in AD occurs to a larger extent than that accounted for age-related GC-IPL loss alone (about 0.3 μm/ year) [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…Laser Doppler studies have shown altered retinal blood flow in patients with AD, although no correlation was found between RNFL thickness and retinal blood flow [45]. Two recent studies using retinal photography found retinal vascular abnormalities, including vascular attenuation, reduced branching pattern, and altered venular tortuosity [54,56,57]. According to the authors, these retinal vascular changes in AD may be correlated with the neocortical amyloid plaque burden [58] or may mirror the cerebral microvascular pathology [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…The parameter λ controls the strength of regularization. The parameter α is the elastic-net regularization mixing parameter; α = 1 corresponds to the lasso (also known as L 1 regularization) whereas α = 0 corresponds to ridge regression (L 2 regularization) [8]. For highly correlated features, the lasso tends to pick one of the features and discard the others, whereas the ridge shrinks the feature coefficients towards each other.…”
mentioning
confidence: 99%
“…For highly correlated features, the lasso tends to pick one of the features and discard the others, whereas the ridge shrinks the feature coefficients towards each other. Elastic net mixes the two; for example, α = 0.5 tends to select or exclude groups of highly correlated features together [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation